2021
DOI: 10.1038/s41598-021-90371-8
|View full text |Cite
|
Sign up to set email alerts
|

A covered eye fails to follow an object moving in depth

Abstract: To clearly view approaching objects, the eyes rotate inward (vergence), and the intraocular lenses focus (accommodation). Current ocular control models assume both eyes are driven by unitary vergence and unitary accommodation commands that causally interact. The models typically describe discrete gaze shifts to non-accommodative targets performed under laboratory conditions. We probe these unitary signals using a physical stimulus moving in depth on the midline while recording vergence and accommodation simult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 89 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…Despite that Helmholtz's opposing theory was postulated contemporaneously with Hering's, critical experiments differentiating these theories are lacking, and Hering's theory has managed to prevail for over 150 years. However, recent results of experiments comparing oculomotor behavior of both eyes during monocular viewing challenge Hering's Law [23]. This study found asymmetric behavior between the two eyes during smooth pursuit of a midline target, evidence that the eyes are not yoked.…”
Section: Introductionmentioning
confidence: 52%
See 4 more Smart Citations
“…Despite that Helmholtz's opposing theory was postulated contemporaneously with Hering's, critical experiments differentiating these theories are lacking, and Hering's theory has managed to prevail for over 150 years. However, recent results of experiments comparing oculomotor behavior of both eyes during monocular viewing challenge Hering's Law [23]. This study found asymmetric behavior between the two eyes during smooth pursuit of a midline target, evidence that the eyes are not yoked.…”
Section: Introductionmentioning
confidence: 52%
“…This study was conducted to investigate xation behavior of both eyes under binocular and monocular viewing. We wished to determine whether the eyes behaved the same or differently motivated by results of previous work showing asynchronous and unpredictable behavior of an occluded eye during midline pursuit [23].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations